The role of force-sensing devices in spinal manipulative therapy research, education, and clinical practice. - Funabashi, Martha; Starmer, David; Smith, Nicole M.; Choi, Grand; Dane, Andrew; Downie, Aron S.; Duarte, Felipe C. K.; Hollandsworth, Dana; Malaya, Christopher A.; Pagé, Isabelle; Nim, Casper (Journal of the Canadian Chiropractic Association, 2025)
Spinal manipulative therapy (SMT) is commonly used by chiropractors, and much attention has been given to teaching students how to master it. Currently, over 20 chiropractic educational institutions use some type of force-sensing device (FSD) to teach students how to modulate their SMT force-time characteristics. Modulating SMT forces is believed to improve SMT's effectiveness, increase comfort during SMT, and reduce adverse events, contributing to improved clinical outcomes. In this commentary, we highlight the transition we are currently living in and discuss the strengths, uncertainties and opportunities of using FSDs to modulate SMT force-time characteristics within research, education, and clinical practice. Given that additional high-quality research is needed to determine if the ability to modulate SMT force-time characteristics indeed influences clinical effectiveness, increases patient comfort, and reduces adverse events, a collaborative effort is needed to address these critical research gaps. Specifically, having similar FSDs across educational institutions allows the collection of multicenter data, sharing research findings across different settings, and provides a unique opportunity for advancing educational and clinical research.